Adsorptive Studies Of Bovine Serum Albumin (BSA) By PES-HAP-PVP Mixed Matrix Membrane - Hanifa, Nurul Husna Elyana (Universiti Sains Malaysia, 2017)
Hydroxyapatite (HAP) as adsorptive particles embedded into Polyethersulfone (PES) Mixed Matrix Membranes (MMMs) were successfully prepared, in order to study the adsorption behavior of Bovine Serum Albumin (BSA) as protein model in this system. Membranes with different PES and different HAP concentrations were prepared by phase inversion method. All the prepared membranes were characterized through Fourier Transform Infrared Spectroscopy (FTIR) analysis, Scanning Electron Microscope (SEM) analysis, Contact Angle measurement (CA), water content and overall porosity. From the FTIR spectra, peak at 1011.04 cm-1 was attributed to chemical properties of HAP particle which indicates that the HAP particle was successfully impregnated into PES mixed matrix membranes. Membranes structure analysed through SEM confirmed that the surface pores enlarged with reducing the PES concentration and the surface pores became smaller with the addition of HAP particles into PES mixed matrix membranes. Water content was increased with increasing of PES concentration and increased the hydrophilicity of the MMMs, which partly caused by the increase in overall porosity of the MMMs. Adsorption experiment was carried out to investigate the effect of PES and HAP concentrations on BSA adsorption. The initial concentration and contact time in a batch system was varied with constant shaking rate of 90 rpm for all the prepared membranes. The membranes with lowest PES concentration at 14 wt% PES concentration showed the highest adsorption capacity towards BSA. The highest HAP of 80 wt% gave the highest adsorption capacity of 0.240 g BSA/g membrane of maximum adsorption capacity. The 14 wt% PES concentration with 60 wt% and 80 wt% of HAP concentration of PES concentration were chosen to dynamic BSA adsorption onto membrane. The xiv optimum concentration for initial BSA concentration at 1.5 g/L was chosen as equilibrium BSA concentrations. For equilibrium studies, two analytical adsorption isotherms, Langmuir and Freundlich models were fitted to equilibrium adsorption data. PES/HAP/PVP MMMs shows that The Langmuir isotherms model was the best fitted data to describe the BSA adsorption process. For kinetic studies, the 14 wt% PES concentration with 60 wt% and 80 wt% of HAP concentration of PES concentration were found to agree with pseudo-second-order kinetics model. Regeneration of membranes were carried out by shaking the used membrane in acetate buffer solution at pH 4.2 and the result demonstrated for 14 wt% PES concentration with 60 wt% and 80 wt% of HAP concentration of PES concentration that, there is no significant reduction in the adsorption capacity.